Hubungan Antara Disiplin Kerja Dengan Produktivitas Kerja Pada Karyawan PT.Sinar Niaga Sejahtera RegionalJateng 2 Jogjakarta - Tri Astuti Istiqomah, Riyana; , Drs. Mohammad Amir,M.Si (2016)
The employee's productivity is important because it is used as a measurement of success running the business in a company. Labor discipline is one of the factors that can affect work productivity of employees. This study aims to: 1) Determine the relationship between the discipline of work with labor productivity in employees, 2) To determine the effective contribution of labor discipline on work productivity in employees, 3) To determine the level of labor productivity in employees, 4) To determine the level of work discipline on employees. This study uses the entire employee population saleman Sinar Niaga Sejahtera Regional Jateng 2 Jogjakarta totaling 42 people were used as samples, so in this study is called a population study. Data collection tool used is the scale of work discipline and documentation productivity. Methods of data analysis using non-parametric statistical techniques kendall's-tau. Based on the calculation, the value of the correlation coefficient (r) of 0.538 with a (p) = 0.000 (p <0.01) means there is a significant positive relationship between the discipline of working with labor productivity. The effective contribution of these two variables is shown by the determinant coefficient (r²) = 0.289 which shows that the discipline of work affects work productivity by 28.9% and 71.1%, the rest is influenced by other variables. Variable work discipline has the empirical mean (RE) of 96.43 and the mean hypothetical (RH) of 75 which means that the discipline of work on employees is high. Variable labor productivity has the empirical mean (RE) A sum of 2.38 and the mean hypothetical (RH) of 3, which means the employees work productivity is low. Keywords: work discipline. work productivity